2020
DOI: 10.1080/21655979.2020.1860479
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide survey of interaction between rice and Magnaporthe oryzae via microarray analysis

Abstract: The main aim of the work is to study the regulation of gene expression in the interaction between rice and Magnaporthe oryzae by gene chip technology. In this study, we mainly focused on changes of gene expression at 24, 48, and 72 hours post-inoculation (hpi), through which we could conduct a more comprehensive analysis of rice blast-related genes in the process of infection. The results showed that the experimental groups contained 460, 1227, and 3937 significant differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…But no reports related to serious diseases found till now. Previous study described the number and type of the pro-inflammatory strain surface protein SlpA that may relate to toxic behavior in C. difficile [ 14 , 36 , 37 ]. The genomic information was provided in present study confirmed that C. difficile LCL126 has some relevant toxin genes, while in-depth study of its metabolome and functional genes needs to be further studied to explore the toxicological mechanism of C. difficile LCL126, aimed to improve the comprehensive understanding of microorganisms and promote the C. difficile related infectious diseases.…”
Section: Resultsmentioning
confidence: 99%
“…But no reports related to serious diseases found till now. Previous study described the number and type of the pro-inflammatory strain surface protein SlpA that may relate to toxic behavior in C. difficile [ 14 , 36 , 37 ]. The genomic information was provided in present study confirmed that C. difficile LCL126 has some relevant toxin genes, while in-depth study of its metabolome and functional genes needs to be further studied to explore the toxicological mechanism of C. difficile LCL126, aimed to improve the comprehensive understanding of microorganisms and promote the C. difficile related infectious diseases.…”
Section: Resultsmentioning
confidence: 99%